Swirl stability and emission characteristics of CO-enriched syngas/air flame in a premixed swirl burner - Samiran, N. A.; Ng, Jo-Han; Mohd Jaafar, Mohammad Nazri; Valera-Medinad, Agustin; Tung, Chong Cheng (Elsevier, 2017)
There is significant variation in the composition of synthesis gas derived from biomass, coal or waste. The inconsistency of syngas constituents poses challenges and requires thorough characterisation prior to use as alternative fuel in practical combustion system. The present study investigates the combustion and emission characteristics of CO-enriched syngases by using an atmospheric premixed swirl flame burner. High (CO/H2 = 3) and moderate (CO/H2 = 1.2) CO-enriched syngases were fully premixed with air and diluents of CH4 and CO2 prior to ignition atthe burner outlet. Direct flame imaging shows that moderate CO-enriched syngas produces less luminous flames than high CO-rich syngas, signifying less tendency to form soot. Moderate CO-rich syngases show more compact flames with higher intensity owing to higher H2 contents. The blowout test shows that higher CO content syngases result in lean blowout at higher equivalence ratios, posing stability issues. High fractions of unreactive CO2 and reactive CH4 in syngases result in higher lean blowout limit. Emissions wise, high CO-rich syngases show evidently less NOx emissions as compared to baseline pure CO flames at increasing equivalence ratios. Moderate CO-rich flame exhibits higher NOx level than high CO-rich at < 0.8. However, at fuel-stoichiometric and fuel-rich regions they display similar levels of NOx. Higher fraction of CO2 dilution results in reduction of NOx emissions, with pronounced impact on fuel-rich cases. There was minimal effect on CO emissions with increased dilution of CO2.